Research on user needs for mobile information services in Chinese university libraries: comparison between existing users and potential users. Issue 4 (1st August 2016) - Zhao, Yang; Deng, Shengli; Gao, Ting; Zhou, Ruoxin
Abstract : Purpose: This paper aims to investigate the service demand of existing users and potential users for mobile information services provided by university libraries in China. The primary objective is to explore the impact of user experience on user needs, which is conducted by a comparison between two user groups over their needs from three aspects –service function, service mode and information content. Design/methodology/approach: Data were collected from 353 library users from ten Chinese universities via questionnaires. Based on the user needs model, three dimensions of user needs were established for mobile information services and 26 measurement items were generated through a review of the literature. Furthermore, based on frequency analysis, independent samples t-test, and the calculation of need rate, the demand differences in mobile information services between existing and potential users were explored. Findings: Significant differences existed in the needs for service functions and service modes of mobile information services between existing users and potential users. Existing users cared more about such characteristics as intelligence, personalization, and the variety of mobile services; Potential users, by contrast, concerned themselves more with the usability of mobile services and similarity to traditional information services. These two user groups showed little difference in the needs for information content as they both have strict requirements for specialty, richness in and quality of information resources in mobile network environments. Originality/value: Previous research on user needs for mobile libraries services has been primarily conducted from the perspectives of existing users. This study, however, compared the needs of existing and potential users based on their previous experiences, which can help libraries to know better what their users need and improve the quality of mobile information services to meet those needs. This can also make existing users more willing to use the services and cultivate the usage habits of potential users at the same time.